Descriptions and outcomes of cardiac evaluations in pediatric patients hospitalized for asthma. (1st November 2020) - Parlar-Chun, Raymond; Kakarala, Kokila; Singh, Mani
Abstract: Objective: Patients hospitalized for asthma can exhibit concurrent cardiac symptoms and undergo cardiac work up. We identify patients admitted for asthma that underwent cardiac workup and describe outcomes to evaluate the utility of cardiac testing in this population. Methods: Patients aged 4 to 17 years admitted for status asthmaticus from 2012 - 2016 were screened for EKG, ECHO, or cardiac enzyme obtainment. Results: Out of 1296 patients, 77 (6%) received cardiac testing. The most common reasons for testing were chest pain (25, 32%), blood pressure abnormalities (11, 14%), tachycardia (8, 10%), arrhythmia (6, 8%), and syncope (6, 8%). Sinus tachycardia (43, 66%) was the most common EKG finding. 4 out of 27 patients who underwent ECHOs had abnormalities: 2 with hypertrophic cardiomyopathy (HCM), 1 with vascular ring, and 1 with evidence of pulmonary hypertension. All patients who underwent an EKG to evaluate tachycardia had normalization of heart rate at discharge. Cardiac ischemia was not evident in any patients who underwent workup with cardiac enzymes to evaluate chest pain. All cases of arrhythmias resolved on discharge. Diastolic hypotension (DhTN) was found in 10 out of the 11 blood pressure abnormalities. There was mixed efficacy of fluid bolus in correcting DhTN. All DhTN resolved on discharge. One patient with syncope had a new diagnosis of HCM. Conclusions: While cardiac complications are seen in patients admitted for status asthmaticus, the etiology rarely stems from underlying cardiac disease. EKGs, ECHOs, and cardiac enzymes should have a minimal role in the management of the hospitalized asthmatic patient.